Tectonic ecology of the temperate forests of South America and New Zealand - Veblen, Thomas (2016)
Ecological disturbances triggered by earthquakes and volcanic eruptions are of fundamental importance in structuring the temperate forests of southwestern South America and New Zealand. We review studies of the ecological effects of these tectonic phenomena and how they have been central to progress in the modern development of forest ecology in both regions. Studies of tectonic influences on the dynamics of southern temperate rainforests of Chile and New Zealand published in the 1970s and early 1980s contributed prominently to the shift away from the equilibrium paradigms dominant globally in the 1960s and towards modern non-equilibrium frameworks of forest dynamics. Empirical studies of tectonic ecology in these temperate forests in combination with critical evaluations of earlier successional theory have significantly advanced understanding of the roles of coarse-scale disturbance in the dynamics of forests in southwestern South America and New Zealand. Recognition that cohort forest structures triggered by exogenous disturbances such as wind storms and tectonic events are the norm rather than all-aged structures has been of fundamental importance to understanding the dynamics of these forests. The non-equilibrium patch dynamics framework for interpreting forest structure and dynamics bolstered by tectonic ecology studies in southern South America and New Zealand was of key importance in refining older views of these forests as being out of equilibrium with contemporary climate, revising understanding of the effects of introduced browsing animals on forest structure, and guiding the development of appropriate forest management practices.